2017
DOI: 10.3324/haematol.2017.164632
|View full text |Cite
|
Sign up to set email alerts
|

The BET bromodomain inhibitor CPI203 improves lenalidomide and dexamethasone activity in in vitro and in vivo models of multiple myeloma by blockade of Ikaros and MYC signaling

Abstract: Most patients with multiple myeloma treated with current therapies, including immunomodulatory drugs, eventually develop relapsed/refractory disease. Clinical activity of lenalidomide relies on degradation of Ikaros and the consequent reduction in IRF4 expression, both required for myeloma cell survival and involved in the regulation of MYC transcription. Thus, we sought to determine the combinational effect of an MYC-interfering therapy with lenalidomide/dexamethasone. We analyzed the potential therapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…MYC activation is associated with hyperdiploid MM and shorter survival, and also plays a causal role in the progression of monoclonal gammopathy to multiple myeloma. MYC protein overexpression is a feature of progression and adverse prognosis in multiple myeloma [42][43][44][45]. In recent research, it was also proved that sialyltransferase inhibition leads to inhibition of tumor cell interactions with VCAM1, and improves survival in a human multiple myeloma mouse model [46].…”
Section: Discussionmentioning
confidence: 99%
“…MYC activation is associated with hyperdiploid MM and shorter survival, and also plays a causal role in the progression of monoclonal gammopathy to multiple myeloma. MYC protein overexpression is a feature of progression and adverse prognosis in multiple myeloma [42][43][44][45]. In recent research, it was also proved that sialyltransferase inhibition leads to inhibition of tumor cell interactions with VCAM1, and improves survival in a human multiple myeloma mouse model [46].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the possibility of combinatorial block of MYC and IRF4 gene expression was greatly advanced by the demonstration that treatment of multiple myeloma tumor cells with the BET-bromodomain inhibitor JQ1 led to loss of BRD4 at super-enhancers, and consequent transcription elongation defects of genes with super-enhancers, including MYC and IFR4 [ 62 ]. Indeed, numerous studies have demonstrated, both in vitro and in vivo, the synergistic antitumor activity of IMiDs and BET-bromodomain inhibitors [ 63 , 64 , 65 , 66 ]. We observed that the combination of pomalidomide with the BET family antagonist JQ1 has additive effects in four of five pomalidomide-insensitive cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐MM effects of BET inhibitors result from their inducing cell growth arrest and caspase‐mediated apoptosis by downregulation of c‐MYC transcription and concurrent genomewide downregulation of c‐myc target genes in MM cells . The BRD inhibitor CPI203 overcame melphalan and bortezomib resistance of MM cells in vitro, and in combination treatments, CPI203 synergized with bortezomib and melphalan as well as lenalidomide and dexamethasone regimens to induce apoptosis of MM cell lines . Although none of these studies measured the effects of BRD inhibitors on development of MM bone lesions, Diaz and colleagues tested the effectiveness of the BRD inhibitor CPI203 on primary patient CD138+ MM cell survival in cocultures with BMSCs.…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 99%
“…The BRD inhibitor CPI203 overcame melphalan and bortezomib resistance of MM cells in vitro, and in combination treatments, CPI203 synergized with bortezomib and melphalan as well as lenalidomide and dexamethasone regimens to induce apoptosis of MM cell lines . Although none of these studies measured the effects of BRD inhibitors on development of MM bone lesions, Diaz and colleagues tested the effectiveness of the BRD inhibitor CPI203 on primary patient CD138+ MM cell survival in cocultures with BMSCs. In these experiments, CPI203 prevented BMSC‐mediated protection from the cytotoxic effects of the drug as well as the increased proliferation of MM cells usually found in BMSC cocultures.…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 99%